A Study of Living Godess Kumārī: The Source of Cultural Tourism in Nepal (The Gaze: Journal of Tourism and Hospitality, 2018)
The Kumārī- living goddess, as the spirit of the goddess of power believed to be embodied in a long succession of Nepali virgin girls, has been worshiped for centuries. The Kumārī is a prepubescent girl who is hailed as manifestations of divine and spiritual energy, the living incarnation of the Hindu goddess of power; for Buddhist devotees, the Kumārī is a manifestation of Vajradevi or Tara. The most important requirement is that the girl has never menstruated. Hindu and Buddhist devotees bow their forehead on the toes of the living goddesses the Kumārī with high level of respect to fulfil their wishes. The Kumārī is commonly “Mother Deity or Kumārī ma”. As a Mother Deity it is believed that the Kumārī can transmit power or śakti directly into the bodies of those devotees who come to have her audience (darśana). The Kumārī culture is Nepali’s identity and historical cultural heritage. The Kumārī culture has a huge potential to develop cultural tourism in Nepal however, it has not been well-known to the rest of the world adequately. It is one of the country’s oldest tradition and should be preserved.The Gaze: Journal of Tourism and Hospitality Vol.9 2018 p.23-42